Feeding the gut microbiome: impact on multiple sclerosis - Bronzini, Matteo; Maglione, Alessandro; Rosso, Rachele; Matta, Manuela; Masuzzo, Federica; Rolla, Simona; Clerico, Marinella (Frontiers in Immunology, 2023)
Multiple sclerosis (MS) is a multifactorial neurological disease characterized by chronic inflammation and immune-driven demyelination of the central nervous system (CNS). The rising number of MS cases in the last decade could be partially attributed to environmental changes, among which the alteration of the gut microbiome driven by novel dietary habits is now of particular interest. The intent of this review is to describe how diet can impact the development and course of MS by feeding the gut microbiome. We discuss the role of nutrition and the gut microbiota in MS disease, describing preclinical studies on experimental autoimmune encephalomyelitis (EAE) and clinical studies on dietary interventions in MS, with particular attention to gut metabolites–immune system interactions. Possible tools that target the gut microbiome in MS, such as the use of probiotics, prebiotics and postbiotics, are analyzed as well. Finally, we discuss the open questions and the prospects of these microbiome-targeted therapies for people with MS and for future research.